2017
DOI: 10.1186/s13018-017-0526-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxidative stress induced by intracranial iron overload on central pain after spinal cord injury

Abstract: BackgroundCentral pain (CP) is a common clinical problem in patients with spinal cord injury (SCI). Recent studies found the pathogenesis of CP was related to the remodeling of the brain. We investigate the roles of iron overload and subsequent oxidative stress in the remodeling of the brain after SCI.MethodsWe established a rat model of central pain after SCI. Rats were divided randomly into four groups: SCI, sham operation, SCI plus deferoxamine (DFX) intervention, and SCI plus nitric oxide synthase (NOS) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…SCI may cause intracranial iron overload through the NOS–iron-responsive element/IRP pathway, resulting in central pain mediated by the oxidative stress response. 38 Other findings showed that high intracellular iron accumulation in macrophages had induced TNF expression. 17 Thus, iron accumulation after SCI may also contribute to the activation of microglial.…”
Section: Discussionmentioning
confidence: 99%
“…SCI may cause intracranial iron overload through the NOS–iron-responsive element/IRP pathway, resulting in central pain mediated by the oxidative stress response. 38 Other findings showed that high intracellular iron accumulation in macrophages had induced TNF expression. 17 Thus, iron accumulation after SCI may also contribute to the activation of microglial.…”
Section: Discussionmentioning
confidence: 99%
“…Ferroptosis is different from apoptosis, necroptosis, autophagy and other reported cell death methods [4]. levels in the injured area, and iron overload further increases the accumulation of reactive oxygen species (ROS) [5]. In vivo study has demonstrated that ions play a very important role in the early stage of secondary SCI, and enhances production of hydroxyl radicals [6].…”
Section: Introductionmentioning
confidence: 99%
“…Although iron is necessary for normal nerve function, iron overload aggravates secondary damage after nerve injury. Local hemorrhage in the acute phase of SCI leads to a significant increase of iron levels in the injured area, and iron overload further increases the accumulation of reactive oxygen species (ROS) [ 5 ]. In vivo study has demonstrated that irons play a very important role in the early stage of secondary SCI and enhance production of hydroxyl radicals [ 6 ].…”
mentioning
confidence: 99%
“…Another important point we have to point out is that although our study is limited to aged male mice, the anti-aging effects of GDF11 are expected similarly applicable for female mice. The “free radical damage theory” suggests that excess ROS can cause oxidative damage to the macromolecules of cells, including DNA, RNA, proteins, carbohydrates and lipids (Beckman and Ames 1998 ; Giordano et al 2013 ), thus it is applicable for all multicellular organisms at cellular level (Beckman and Ames 1998 ; Finkel and Holbrook 2000 ; Larsen 1993 ; Meng et al 2017 ). As mentioned above, rGDF11 exerts its rejuvenation and anti-aging activity through suppression of ROS production, which is thus believed to equally benefit to both male and female mice.…”
Section: Discussionmentioning
confidence: 99%